What Is 'Kariera'? Detecting Systems and Overlap in Australian Kinship Using the AustKin Database. Issue 2 (14th May 2017) - McConvell, Patrick; Hendery, Rachel
Abstract : Radcliffe‐Brown introduced the concept of a 'Kariera' type of kinship system in proposing his highly influential typology of Australian social organization, building on his earlier reports of fieldwork in the Pilbara of northern Western Australia, in which the Kariera (Kariyarra) people were taken to represent a widespread type. Radcliffe‐Brown's and other typologies of Australian kinship have generally disregarded the universalist categorizations (going back to Fison and Howitt's assignment of Kariera‐type systems to the Dravidian category), in favour of a scheme based on Australia alone. In the spirit of Radcliffe‐Brown's typology, we propose a diagnostic pattern of kinship term equivalences for grandkin such as FF = MMB ( father's father is equivalent to mother's mother's brother ), which can be operationalized in search‐map routines of a database known as AustKin and closely approximates to the set of systems generally recognized as 'Kariera'. However another property of many Kariera grandkin systems which has been claimed to be criterial by some scholars – equivalence between grandkin and grandchild generations (+2 and −2), or Alternate Generation Equivalence – is shown to be more widespread than Kariera and independent of it. With regard to the −1 generation (children and niblings), the pattern among the Kariyarra and more generally in the western Pilbara and Western Desert (where 'son' and 'daughter' are distinguished) is radically different from the pattern found in the other 'Kariera' systems across the rest of the continent, (where 'woman's child' vs. 'man's child' is the prime distinction). This prompts analysis of the child patterns as independent of the Kariera system. This article also shows how the Kariera system is independent of the four‐section system with which it has been claimed to be related functionally, with sections being a later development. We also encounter overlaps, where more than one equivalence pattern intersect in one language, and overlays, where the variation between more than one equivalence also has social contextual functions. Examples of overlaps analysed here are (1) between Kariera and Aluridja (the Western Desert pattern with cross‐parallel neutralization); and (2) between Kariera and a more radical kind of Alternate Generation Equivalence, where parallel grandkin and grandchildren kin‐types are called siblings (generation 0).